2015
DOI: 10.3390/su71215817
|View full text |Cite
|
Sign up to set email alerts
|

Field and Evaluation Methods Used to Test the Performance of a Stormceptor® Class 1 Stormwater Treatment Device in Australia

Abstract: Field testing of a proprietary stormwater treatment device was undertaken over 14 months at a site located in Nambour, South East Queensland. Testing was undertaken to evaluate the pollution removal performance of a Stormceptor treatment train for removing total suspended solids (TSS), total nitrogen (TN) and total phosphorous (TP) from stormwater runoff. Water quality sampling was undertaken using natural rainfall events complying with an a priori sampling protocol. More than 59 rain events were monitored, of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The improved removal rates are believed to be the result of the unique experimental design that excluded potential short-circuiting and specifically focused on evaluating the pollution removal performance of the field-scale FTW alone, rather than as part of a stormwater treatment train. The calculated pollution removal proportions from outflows were found to be less than the values specified by the local Queensland State Planning Policy and regulations (TSS 80%, TP 60%, and TN 45%) [21], and this is likely a reflection of the small FTW footprint as a percentage of the contributing catchment [22]. Calculations of the ER for TN were particularly variable.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The improved removal rates are believed to be the result of the unique experimental design that excluded potential short-circuiting and specifically focused on evaluating the pollution removal performance of the field-scale FTW alone, rather than as part of a stormwater treatment train. The calculated pollution removal proportions from outflows were found to be less than the values specified by the local Queensland State Planning Policy and regulations (TSS 80%, TP 60%, and TN 45%) [21], and this is likely a reflection of the small FTW footprint as a percentage of the contributing catchment [22]. Calculations of the ER for TN were particularly variable.…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that TSS and TP outflow concentrations were significantly lower than inflow concentrations (p < 0.05) ( Table 5). These results demonstrate how highly-variable environmental data may require very large datasets to establish pollution removal efficiencies that are statistically significant using the traditional calculations [22]. Equation (6) was used to estimate the number of samples required to ensure a statistical relevant result (Table 6).…”
Section: Resultsmentioning
confidence: 99%
“…The catchment drainage area consisted of sealed car parks (50%), building roofs (35%), and approximately 15% open space containing lawns and intermittent impervious paved surfaces (concrete pathways). In South East Queensland, field testing of a stormwater treatment device was undertaken over 14 months to evaluate the pollution removal performance of a Stormceptor Class 1 stormwater treatment device [13]. The site comprised a total area of 2800 m 2 , of which 66% roof area, 33% impervious concrete driveway, and 1% landscaped area.…”
Section: Introductionmentioning
confidence: 99%
“…Pollution loads per unit area of NPS pollutants which are discharged in urban areas, are highly concentrated compared to other land-use characteristics, and they contain organic matter, nutrients, and heavy matter, as well as toxic substances. In general, the loads of biochemical oxygen demand (BOD) and suspended solids (SS) in the NPS pollutants have increased 92 times and 24 times respectively compared to the loads in the non-developed region [1][2][3][4]. Among land-use in urban areas, areas with many parks and grasslands release less pollutants compared to commercial and industrial areas.…”
Section: Introductionmentioning
confidence: 99%